Nanohybrid Materials Based on Carbon Nanotubes Encapsulating Catalytic Nanoparticles: Elaboration, Characterization & Applications - Khairul Anwar B Muhamad, Khairul Anwar (Universiti Teknologi Petronas, 2009)
This report basically discusses the research done and understanding of the chosen topic, which is Nanohybrid Materials Based on Carbon Nanotubes Encapsulating Catalytic Nanoparticules: Elaboration, Characterization & Application. The aim of this project is to create nanohybrid material that will increase efficiency and performance of the existence material. The pristine Multi-Walled Carbon Nanotubes (MWNT) will be oxidized first with acid nitric through acid treatment. Metal oxide will be encapsulated inside the Multi-Walled Carbon Nanotubes (MWNT) by using hydrothermal route. Characterization techniques such as Scanning Electron Microscopy (SEM), Fourier Transform Infrared (FTIR), Thermo Gravimetric Analysis (TGA), Transmission Electron Microscopy (TEM), and X-Ray Diffraction (XRD) are being used to investigate the structure of the carbon nanotubes. From the characterization results, it is clearly can be seen that after the acid treatment reaction, the tip of the tube is open for Multiwalled nanotubes (MWNT) while it is close for pristine single walled nanotubes (SWNT). Also, from the FTIR result, it is proven that ZnO were introduced or encapsulated inside the MWNT after simple hydrothermal route reaction. Finally, the application of this nanohybrid material will be elaborated